Avaliação do impacto do Programa Farmácia Popular em uma rede independe de drogarias - Batista, Natalia Bousquet (2015)
Despite the Brazil rely on free public distribution model of drugs, representing progress compared to most developing countries, the overall scenario presents problems of many orders. The public supply is flawed and inefficient, with poorly motivated professionals. This condictions results in losses arising from deviations, poor condition of inadequate storage and distribution processes. The use of private distribuition through Programa Farmácia Popular do Brasil, to the government's point of view, promotes capillary in attendance, increasing social welfare and reduces costs by using staff. From the point of view of society, increases the drug access to the population. Thus, the program has represented an efficient solution for the distribution of medicines in the country. However, from a business point of view, the results of the use of private mesh for the free distribution of medicines are still less described. This study aims to assess the impacts related to the accreditation in the federal program in independent pharmacy chains and private drugstores free distribution of medicines to the population. It addresses a multifunctional matter, and consist of one program analysis that is part of the federal government guidelines and be an unprecedented nature theme with focus on the business environment. From a business point of view, the service to the distribution of free drug program in compliance with the federal government program may represent a business leverage factor to bring potential customers to the establishment. However, it is necessary adaptations occurring in cash flow management to support the possible delays in the transfer of government and meet the supply of medicines to the growing demands. So drugstores inserted in the pharmaceutical retail sector in developing cities acquire competitive advantage and provide greater value to their customers. The free distribuition project implies generalized net benefits. For the population, the direct and effective access. For the private sector, market expansion and the stability of demand. For the government, the replacement of a strategy that converges to the economic, social and political friction.